(untitled) (Papeles, 2022)
The objective of this study is to evaluate the socio-emotional impact of the pandemic in a group of teachers from the city of Pichilemu in the Libertador Bernardo O’Higgins Region in Chile, through discourse analysis establishing the degree of impact on their quality of teaching life as a result of the restriction measures imposed by the health authority added to the implementation of distance education. The changes experienced and their effects at the social, family and work level produced by the suspension of face-to-face classes and the implementation of various digital platforms to continue the educational process are analyzed. The research is carried out from the qualitative paradigm through the Grounded Theory methodology and the constant comparative method through the analysis of in-depth interviews with the use of the ATLAS.ti software. Convenience sampling was used with the participation of 5 teachers with whom the theoretical saturation of the sample occurred. The results obtained from the qualitative analysis of the data generated ten codes and the emergence of four families or categories called emotional effects, resilience, socio-family effects and criticism of institutional management. The health crisis and the restriction of mobility provoke in the interviewees a state of mental, social and physical vulnerability; uncertainty due to the lack of certainty about the future, development of resilience, capacity for self-criticism and adaptive response to the new setting.